Simulation of a SAW-based WLAN using chirp-pi/4 DQPSK modulation - Gugler, Wolfgang; Springer, Andreas; Kuepfer, H.P.; Weigel, Robert (1998 IEEE Ultrasonics Symposium, 1998)
We report on the simulation of a wideband (>50 MHz) spread spectrum system with a spreading bandwidth greater than the coherence bandwidth of the radio channel. SAW filters are used to produce the desired spread spectrum signals (chirp signals) and for matched filtering. Center frequency, transmission bandwidth, and chirp rate of the system are 348.8 MHz, 80 MHz, and ±160 MHz/μs, respectively. By using weighted chirps to reduce the sidelobes of the compressed pulse to -22 dB, π/4 DQPSK modulation as well as overlapping chirp signals, we get a data rate of more than 70 Mb/s. Considering a channel as suggested in the IEEE 802.11 standard for the indoor environment we achieve an improvement of the bit-error-rate (BER) over traditional π/4 DQPSK modulation because of the processing gain due to the pulse compression. The limiting factors of the data rate were found to be intersymbol interference and multipath fading.
elib2cris::1512001600,gugler1998a